2019
DOI: 10.1186/s12868-019-0533-5
|View full text |Cite
|
Sign up to set email alerts
|

Mouse corticospinal system comprises different functional neuronal ensembles depending on their hodology

Abstract: Background Movement performance depends on the synaptic interactions generated by coherent parallel sensorimotor cortical outputs to different downstream targets. The major outputs of the neocortex to subcortical structures are driven by pyramidal tract neurons (PTNs) located in layer 5B. One of the main targets of PTNs is the spinal cord through the corticospinal (CS) system, which is formed by a complex collection of distinct CS circuits. However, little is known about intracortical synaptic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Here, we describe in the mouse that CSp neurons projecting to the cervical spinal cord are anatomically broadly distributed in the contralateral cortex including motor (M1 and M2) and somatosensory (S1 and S2) cortices. It has been shown that different groups of CSp neurons project, in a segregated manner, to the same segment of the spinal cord in rats (Olivares-Moreno et al, 2017), mice (Asante and Martin, 2013;Kameda et al, 2019;Olivares-Moreno et al, 2019;Steward et al, 2021) and monkeys (Coulter and Jones, 1977). These studies show that CSp tract projections from M1 conspicuously avoid the dorsal horn, while S1 projections preferentially terminate into the dorsal horn.…”
Section: Discussionmentioning
confidence: 97%
“…Here, we describe in the mouse that CSp neurons projecting to the cervical spinal cord are anatomically broadly distributed in the contralateral cortex including motor (M1 and M2) and somatosensory (S1 and S2) cortices. It has been shown that different groups of CSp neurons project, in a segregated manner, to the same segment of the spinal cord in rats (Olivares-Moreno et al, 2017), mice (Asante and Martin, 2013;Kameda et al, 2019;Olivares-Moreno et al, 2019;Steward et al, 2021) and monkeys (Coulter and Jones, 1977). These studies show that CSp tract projections from M1 conspicuously avoid the dorsal horn, while S1 projections preferentially terminate into the dorsal horn.…”
Section: Discussionmentioning
confidence: 97%
“…Corticospinal output is topographically organized: CSNs within regions that control specific body parts preferentially innervate spinal segments containing the circuits that control the muscles for those body parts 2 , 3 , 5 7 . CSNs arising from motor regions of isocortex form synapses spread across intermediate and ventral laminae of the spinal grey, home to premotor spinal interneurons; while sensory cortical CSNs have terminal fields mostly restricted to superficial regions of spinal cord, home to the dorsal horn interneurons that regulate peripheral sensory feedback 8 , 9 . Partly because of this anatomy, motor cortical CSNs have been hypothesized to control the activity of individual muscles or muscle synergies through their direct projections to the spinal cord 10 12 .…”
mentioning
confidence: 99%
“…We provided functional, anatomical, and morphological evidence indicating that two distinct populations of PTNs differentially contribute to motor execution. Previous studies have described the relationships between structure and function in Layer 5 PTNs projecting to different targets (Groh et al, 2010; Rojas-Piloni et al, 2017; Olivares-Moreno et al, 2019). Our data revealed that both classes of PTNs are intermingled in sensorimotor cortices, including M1, and only a small proportion of neurons seem to contact the RN and PN simultaneously.…”
Section: Discussionmentioning
confidence: 99%